Value at risk estimation of a power system including wind generation - Usman, M. Dzulhafizi (2015)
Reckoning the risk of load loss, corresponding to a certain event, into a single MW value can be of premium importance to system operators to quickly initiate a remedial action, if necessary. In this paper, risk to system load loss, due to the inclusion of variable wind generation, is estimated using the value at risk (VaR) concept. Monte Carlo simulation (MCS) is used to construct the wind speed model, through Weibull statistical distribution and a multistate model, as well as the annual load profile, through randomization. A six-bus test system is used to apply the developed notions. Results of incorporating wind turbine generation with the test system, among other conventional generators, have shown that the risk levels increases appreciably. The ease at which the system risk is identified and encapsulated into a quantifiable MW estimate, remains the salient attractive feature of the developed tool.